Induction of specific brain oscillations may restore neural circuits and be used for the treatment of Alzheimer's disease. (22nd June 2021) - Chan, D.; Suk, H.‐J.; Jackson, B.; Milman, N. P.; Stark, D.; Beach, S. D.; Tsai, L.‐H.
Abstract: Brain oscillations underlie the function of our brains, dictating how we both think and react to the world around us. The synchronous activity of neurons generates these rhythms, which allow different parts of the brain to communicate and orchestrate responses to internal and external stimuli. Perturbations of cognitive rhythms and the underlying oscillator neurons that synchronize different parts of the brain contribute to the pathophysiology of diseases including Alzheimer's disease, (AD), Parkinson's disease (PD), epilepsy and other diseases of rhythm that have been studied extensively by Gyorgy Buzsaki. In this review, we discuss how neurologists manipulate brain oscillations with neuromodulation to treat diseases and how this can be leveraged to improve cognition and pathology underlying AD. While multiple modalities of neuromodulation are currently clinically indicated for some disorders, nothing is yet approved for improving memory in AD. Recent investigations into novel methods of neuromodulation show potential for improving cognition in memory disorders. Here, we demonstrate that neuronal stimulation using audiovisual sensory stimulation that generated 40‐HZ gamma waves reduced AD‐specific pathology and improved performance in behavioural tests in mouse models of AD, making this new mode of neuromodulation a promising new avenue for developing a new therapeutic intervention for the treatment of dementia. Abstract :